Hegel’s Theory of the Subject
XIX, 232 p.
Keywords: Hegelian philosophy is now enjoying an enormous renaissance in the English-speaking world. At the very centre of his work is the monumental Science of Logic . Hegel's theory of subjectivity, which comprises the final third of the Science of Logic , has been comparatively neglected. This volume collects 15 essays on various aspects of Hegel's theory of subjectivity. For Hegel, substance is subject . Anyone aspiring to understand Hegel's philosophy cannot afford to neglect this central topic.